2022
DOI: 10.1038/s41420-022-00852-6
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation alleviated cerebral ischemia and reperfusion injury in rats by inhibiting pyroptosis via α7 nicotinic acetylcholine receptor

Abstract: Cumulative evidence suggests that pyroptosis, a new sort of programmed cell death, is closely related to cerebral ischemia/reperfusion (I/R) injury. Our previous studies have testified that vagus nerve stimulation (VNS) was involved in many different neuroprotective and neuroplasticity pathways via α7 nicotinic acetylcholine receptor (α7nAchR), a vital node of the cholinergic anti-inflammatory pathway during cerebral I/R injury. We aimed to determine the neuroprotective effects of VNS through α7nAchR-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Importantly, VN stimulation, used in management of treatment-resistant depression, 85 may be neuroprotective after stroke. 86 Both VN-dependent and T cell-dependent cholinergic signaling regulate Paneth cell’s antimicrobial peptide production and epithelial cell proliferation. 87 VN stimulation activates the α7 nicotinic acetylcholine receptor, an important mediator of the cholinergic anti-inflammatory pathway involved in the response to stroke.…”
Section: Neural Pathwaysmentioning
confidence: 99%
“…Importantly, VN stimulation, used in management of treatment-resistant depression, 85 may be neuroprotective after stroke. 86 Both VN-dependent and T cell-dependent cholinergic signaling regulate Paneth cell’s antimicrobial peptide production and epithelial cell proliferation. 87 VN stimulation activates the α7 nicotinic acetylcholine receptor, an important mediator of the cholinergic anti-inflammatory pathway involved in the response to stroke.…”
Section: Neural Pathwaysmentioning
confidence: 99%
“…It establishes a crucial connection between the brain and the gastrointestinal tract and sends information about the state of the inner organs to the brain, which aids in homeostasis of bodily functions. Vagus nerve stimulation is a promising supportive treatment for refractory depression, posttraumatic stress disorder, and inflammatory bowel disease, inhibits cytokine production, and positively effects beneficial monoaminergic brain signaling in psychiatric conditions, such as mood and anxiety [ 61 , 62 , 63 ], and also for the treatment of traumatically injured brain tissues [ 64 , 65 , 66 , 67 , 68 , 69 ]. Gut bacteria have beneficial effects on mood and anxiety through the bioactive factors they produce, which are transported by the vagus nerve to the brain.…”
Section: Therapeutic Vagus Nerve Stimulationmentioning
confidence: 99%
“…In animal models with cerebral ischemia/reperfusion, VNS had a neuroprotective effect by reducing infarct volume and neurological deficits, partly mediated by its anti-inflammatory properties (13). Our previous findings indeed showed that VNS exerted its neuroprotective effect via the suppression of apoptosis and pyroptosis, as well as through the modulation of neuroinflammation (14,15). Furthermore, VNS was shown to suppress microglia activation and reduce neuroinflammation by regulating the NF-kB pathway (16).…”
Section: Introductionmentioning
confidence: 79%